A Cross Sectional Survey Study of Nirogi Rajasthan w.s.r. Bramha Muhuruta Awakening - Khan, Iqbal; Dixit, Mahesh; Zahir, Ruhi (International Research Journal of Ayurveda & Yoga, 2022)
Background-In present century, lifestyle is significantly changed which is creating lot of instability in physical, mental, spiritual and social health hence beginning of healthy lifestyle with awakening on Brahma Muhurta for good practices is needed for healthy and blissful life. The physical and mental health benefits of waking up early have been mentioned in many literatures. Brahma Muhurta is the second last Muhurta, two Muhurta (one hour thirty six minutes) before sunrise. It is best for good practices like Yoga, Pranayam, Dhyana, Atmagyana, Parmatma gyana, Adhyayana etc. for ultimate achievement. Acharya Vagbhat enlightened that awakening early in morning helps for preserving the health and longevity. Objectives-The present cross sectional survey study was planned to evaluate the effect of Bramha Muhuruta Awakening in healthy individuals. Methods -We conducted this study on the 1500 elderly people aged 60 years and above with good health. Study Design-M.M.M. Govt. Ayurveda College, Udaipur has conducted a cross sectional survey study by the method of questionnaire through direct interview or telephonic method. Results- In this study we found 1306 people (87.07%) awaking at Brahma Muhurta. After that only 1138 (88.91%) have sun exposed and 1005 (87.32%) people go to a day time sleep called Diwa-swapan.